2022
DOI: 10.11591/ijeecs.v25.i1.pp172-182
|View full text |Cite
|
Sign up to set email alerts
|

State and fault estimation based on fuzzy observer for a class of Takagi-Sugeno singular models

Abstract: Singular nonlinear systems have received wide attention in recent years, and can be found in various applications of engineering practice. On the basis of the Takagi-Sugeno (T-S) formalism, which represents a powerful tool allowing the study and the treatment of nonlinear systems, many control and diagnostic problems have been treated in the literature. In this work, we aim to present a new approach making it possible to estimate simultaneously both non-measurable states and unknown faults in the actuators and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…it follows that (46) is equivalent to (29). Finally, according to Lyapunov stability theory, if the LMI conditions (29) are satisfied, the ( 24) is exponentially stable.…”
Section: ❒ Issn: 2088-8708mentioning
confidence: 98%
See 1 more Smart Citation
“…it follows that (46) is equivalent to (29). Finally, according to Lyapunov stability theory, if the LMI conditions (29) are satisfied, the ( 24) is exponentially stable.…”
Section: ❒ Issn: 2088-8708mentioning
confidence: 98%
“…Developing an UIO for T-S fuzzy systems satisfying Lipschitz conditions is the aim of the work presented in [28]. In [29] the authors used the result obtained in [27] to develop a new approach making it possible to estimate simultaneously both non-measurable states and unknown faults in the actuators and sensors for T-S implicit model with MPV.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 4.2: Let (𝑉, 𝑁 ̃𝑓, 𝛥 𝑐 ) be a FRNS with 𝛥 𝑐 is upper semi-continuous. Define: 𝑞 𝛼 (ⱱ 1 ) = 𝑖𝑛𝑓{𝑡 > 0, 𝑁 ̃𝑓(ⱱ 1 , 𝑡) < 𝛼} for 0 < 𝛼 < 1 (6) and 𝑄={𝑞 𝛼 (•), 0 < 𝛼 < 1} then (𝑉, 𝑄) is a GSQNF.…”
Section: Creating Space Of Quasinorm Familymentioning
confidence: 99%
“…Bouassem et al [12] suggested another technique based on the separation between static and dynamic relations in the T-S implicit system to estimate both the system state and the UIs concomitantly. This approach allowed the estimation of both nonmeasurable states and unknown faults in the actuators and sensors for a class of continuous-time T-S implicit models in [13]. Louzimi et al [14], a design of an UIO is proposed for a class of continuous-time T-S implicit systems satisfying the Lipschitz conditions.…”
Section: Introductionmentioning
confidence: 99%